Poor cognitive flexibility, and the experience thereof, in a subclinical sample of female students with obsessive‐compulsive symptoms. Issue 6 (6th October 2014) - Sternheim, Lot; van der Burgh, Maureen; Berkhout, Lotte J.; Dekker, Maria R.; Ruiter, Channah
<x xml:space="preserve">Abstract</x> Research indicates that people with obsessive‐compulsive disorder (OCD) have poor cognitive flexibility. However, studies have largely focused on actual abilities and while individuals' emotional responses may be just as important, little is known about how those with OCD experience a situation that requires cognitive flexibility. It is furthermore largely unknown whether cognitive flexibility may also be important for people with OCD symptoms, rather than only to those with full blown disorders. This study investigates the relationship between cognitive flexibility, and the experience thereof in female students with and without OCD symptoms. It was expected that poor cognitive flexibility would be positively associated to OCD symptoms, and that those with OCD symptoms would display poor cognitive flexibility, and experience situations requiring cognitive flexibility as more difficult, than those without OCD symptoms. Participants completed a measure for OCD symptoms, a neuropsychological task to measure cognitive flexibility, and a self‐report measure assessing emotional experience of situations requiring cognitive flexibility. Positive associations between OCD symptoms and both poor cognitive flexibility and negative experience of situations requiring cognitive flexibility were found. Furthermore, those with OCD symptoms performed poorer on the cognitive flexibility task than those without OCD symptoms, and reported higher scores on the cognitive inflexibility questionnaire. Results confirm a relation between OCD symptoms and poor cognitive flexibility in a subclinical sample and identify a relation between OCD symptoms and a negative experience of situations that require cognitive flexibility. Overall findings suggest that poor cognitive flexibility may be an important part of OCD symptomatology.